Pengaruh Kebijakan Pengelolaan Pegawai terhadap Kinerja Pegawai pada PT Bumi Karsa Kota Makassar - Suryani Alimuddin; M. Akhyar; Sudirman Sudirman; Maryam Maryam (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Human resource management plays a crucial role in improving employee performance amid the increasing competitiveness of the construction industry. Effective employee management policies create a supportive work environment, enhance employee motivation, and improve organizational productivity. This study aims to examine the effect of employee management policies on employee performance at PT Bumi Karsa Makassar. The study employed a quantitative approach using a survey method. The population consisted of all employees of PT Bumi Karsa Makassar, and a census sampling technique was applied, involving all 33 employees as respondents. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, simple linear regression analysis, t-test, and coefficient of determination (R²) with IBM SPSS software. The findings indicate that the research instrument met the validity and reliability requirements. The regression analysis revealed that employee management policy has a positive and statistically significant effect on employee performance, with a regression coefficient of 0.593, a t-value of 4.260 exceeding the critical value of 2.039, and a significance value of 0.000 (<0.05). Furthermore, the coefficient of determination (R²) of 0.372 indicates that employee management policy explains 37.2% of the variance in employee performance, while the remaining 62.8% is influenced by other variables not included in this study. These findings suggest that improving employee management policies through appropriate placement systems, competency development, performance evaluation, reward mechanisms, and continuous employee development can significantly enhance employee performance at PT Bumi Karsa Makassar.